Beyond Nationalism? The Anti-Austerity Social Movement in Ireland: Between Domestic Constraints and Lessons from Abroad. Issue 3 (3rd July 2017) - Dunphy, Richard
ABSTRACT: The European financial crisis has inspired a wave of social activism, challenging established party politics. In Ireland, a large social protest movement produced a Right2Change political campaign in 2015 that confronted the right-wing consensus in Irish politics. Some activists sought to emulate and learn from the example of new parties like Spain's Podemos . Yet, to date, the traditional party structure remains intact, and hopes of emulating the success of activists elsewhere remain muted. At the same time, anti-austerity activism in Ireland has seen a conscious attempt to engage in intense dialogue with the pan-European experience. Irish activists have looked to Europe before for inspiration and a sharing of experiences; but the most recent attempt to create a Europeanised public space in response to the perceived 'blockage' in the Irish party system is something fairly innovative. This article, based in part on ten semi-structured interviews with politicians and social movement activists, considers the achievements and failings of the Irish anti-austerity movement to date.